Dynamic Characterization of High Plinths of Temples in the Kathmandu Valley Using Microtremors. Issue 5 (4th May 2022) - Kawan, Chandra Kiran; Maskey, Prem Nath; Motra, Gokarna Bahadur
ABSTRACT: The 2015 Gorkha earthquake damaged many unreinforced masonry buildings in the UNESCO World Heritage Sites of Kathmandu Valley, such as Kathmandu, Patan, and Bhaktapur. But there were a few multi-tiered temples, with high plinths, that survived the recent earthquake. The temples with a massive high plinth have shown better seismic performance both in past historical earthquakes as well as in the recent 2015 earthquake. In this paper, the results of a reconnaissance survey conducted to assess the seismic effect on the high plinth caused by the 2015 Gorkha earthquake is presented first. Extensive field investigation of excavation works indicates the bulky volume of the traditional construction materials were used to build the high plinth with distinct construction techniques. Second, the dynamic properties of high plinths of nine Nepalese temples measured from microtremor data are presented. The damage assessment shows that the 2015 Gorkha earthquake had minor effects on the plinths. The predominant frequencies obtained at the ground points nearby the temples vary from 0.44–1.32 Hz and predominant frequencies obtained from the H/V spectral ratio ranged 2.88–12.70 Hz. Damping ratios obtained vary from 2.01–8.50%. 1-D wave propagation shows that the plinth act as damping agent.